Sistem Penentuan Dosis Kebutuhan Pupuk Nitrogen Berdasar Warna Daun (Bwd) Pada Tanaman Padi Dengan Sensor Tcs 3200 Berbasis IoT - Rusito; Muhammad Agus Kurniawan (Elkom : Jurnal Elektronika dan Komputer, 2020)
Recent technological developments determine humans to be creative in creating tools that implement technology in it with the aim of facilitating human tasks in daily activities. Inappropriate use of fertilizers can cause losses, both losses on fertilizer, on plants, as well as on the soil and the environment around fertilization. Losses on plants such as unhealthy plant growth and susceptible to disease pests, plant yields are not as expected or low. From the background above, the writer found an idea to create a system or tool that can help farmers in determining the dose of Nitrogen fertilizer in their rice plants, through the storage of the dosage data of each land. The user did five scans, from each scan producing RGB values, each RGB value from five samples was then matched with the BWD dose color indicator. The sample dose results are then sent by the NodeMcu microcontroller to the webserver database. Based on the assessment of the test conducted by 10 Users by Gapoktan Farmers Group of Tosari Kendal Village, the total value of 372 that has been averaged to be 37.2 is between 31 - 40 which is classified in the category of "Very Valid or Very Effective".